Types of pathology and ossicular status in atticoantral disease undergoing mastoidectomy at Bir Hospital - Shrestha, D; Thapa, P; Bhandari, YB (Journal of College of Medical Sciences-Nepal, 2012)
A prospective study was carried out in the department of ENT and Head and Neck Surgery in Bir Hospital, Kathmandu to know the types of the pathology and the ossicular status in atticoantral disease. This study included 100 cases of CSOM (AA) scheduled for routine mastoidectomy. In this study cholesteotoma was the commonest pathology 61 (61%) followed by granulation tissue alone in 27 (27%) cases and both cholesteotoma and granulation tissue were found in 12 (12%) cases. Ossicular damage was more common in CSOM (AA) with granulation tissue in all 27 (100%), 54(58.06%) in CSOM(AA) with cholesteotoma and 12 (12.9%) in CSOM(AA) with both cholesteotoma and granulation tissue. M+S+ ossicular defect was the commonest ossicular defect 47 (50.53%) followed by M+S-24(25.80%), M-S+13(13.97%)and M-S- 9(9.67%) cases. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 26-30 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6722